“Tiga Serangkai” untuk Memprediksi Perusahaan dengan Kesulitan Keuangan Sebelum Masa Pandemi - Qadri, Resi Ariyasa; Khadijah, Ika Mutiara; Uliansyah, Beta Andri Anggiano (E-Jurnal Akuntansi, 2023)
This research aims to foresee financial difficulties in the agricultural industry using three prominent variables: profitability, operating leverage, and liquidity insolvency, before the pandemic. The research employed the documentation technique as the main data collection method. The purposive sampling technique was conducted to obtain the distressed and non-distressed companies during the 2017-2019 period. Multiple discriminant analysis was employed as the data analysis method. Our study reveals that the “big three” factors of profitability, operating leverage, and liquidity insolvency are all capable of differentiating between businesses that are in financial crisis and those that are not. With a model accuracy of 85.700 percent, the “big three” factors can also serve as the determining variables in the discriminant function with profitability as the most influential variable. Keyword: Multiple Discriminant Analysis; Financial Distress; Profitability; Operating Leverage; Liquidity Insolvency